Investigation of the sewing needle size on needle heating - (:unkn) unknown (Fiber Society, 2014)
In this study, a heavy weighted polyethylene (PE) fabric was sewed by three sewing needles in different numbers. Sewing process was carried out at a constant speed. During the sewing process, the heating rate of the needle was measured. The effects of different needle numbers onto the needle heating were investigated. Additionally, the deformation onto the fabric surface stemming from the needle penetration was searched via a light microscopy.
Keywords: Needle heating; Sewing needle; Woolen fabric